The social importance of a kiss: a Honnethian reading of David Levithan's young adult novel, Two Boys Kissing. Issue 6 (1st November 2016) - Carlson, David Lee; Linville, Darla
ABSTRACT: Although trends in young adult literature (YAL) indicate that authors are constructing more positive renditions of gay characters, curricular and pedagogical choices seem to remain quite unsympathetic and "conservative, " reproducing harmful stereotypes. This paper contends that the kiss in YAL can symbolize the physical, social, and moral manifestation of same-sex desire, and thus functions as a personal, social, and moral marker of one's relation to oneself and to others. To aid our discussion, we employ Axel Honneth's theory of recognition. Integrating Honneth's theory of recognition with lesbian, gay, bisexual, trans, queer and questioning (LGBTQ) young adult novels offers researchers the potential to conduct literary analysis that offers readers, teachers, and students new or alternative "readings" of LGBTQ individuals as well as the social constraints that obstruct social recognition for everyone within a given space. This paper provides a brief literature review of LGBTQ YAL in education and then explicates Honneth's theory of recognition, followed by an application of Honneth's theory to David Leviathan's novel, Two Boys Kissing .